Investigation of association between genetic polymorphisms of MMP2, MMP8, MMP9 and TIMP2 and development of varicose veins in the Slovak Population - pilot study - Mazuchová, J; Halašová, E; Mazuch, J; Šarlinová, M; Valentová, V; Franeková, M; Zelník, Š; Krkošková, K; Javorka, K; Péč, M; Grendár, M (Physiological research, 2020)
Matrix metalloproteinases (MMPs) are a family of zinc-dependent metalloendopeptidases that degrades extracellular matrix (ECM) components. MMPs are associated with venous wall remodelling, proliferation, migration, phenotypic and functional transformation of vascular smooth muscle cells and ECM organization under the physiological and pathophysiological conditions. We investigated possible association of genetic promoter polymorphisms of MMP2 (rs243866), MMP8 (rs11225395), MMP9 (rs3918242) and TIMP2 (rs8179090) to varicose veins development in the Slovak population. Genomic DNA from 276 Slovak individuals (138 cases, 138 controls) was genotyped for selected SNPs (rs243866, rs11225395, rs3918242 and rs8179090) using the PCR-RFLP analysis. The data were analysed by chi-squared (chi2) test, logistic regression, and Mann-Whitney test. The risk of varicose veins development was evaluated in dominant, codominant and recessive genetic models. The statistical evaluation of selected polymorphisms in patients in all three genetic models has not shown a significant risk of varicose veins development. Our study has not shown the association between selected polymorphisms and increased risk of varicose veins development in Slovak population. More evidence with broaden sample size is needed.
Keywords: varixy; Polymorphism, Single Nucleotide; Humans; tkáňový inhibitor metaloproteinasy 2; Case-Control Studies; Promoter Regions, Genetic; lidé středního věku; studie případů a kontrol; Matrix Metalloproteinase 8; jednonukleotidový polymorfismus; Female; Aged; mladý dospělý; dospělí; Matrix Metalloproteinases; senioři; lidé; Genotype; Slovakia; Slovenská republika; pilotní projekty; Pilot Projects; Varicose Veins; Adult; matrixové metaloproteinasy; ženské pohlaví; Matrix Metalloproteinase 9; Male; Middle Aged; matrixová metaloproteinasa 9; genetická predispozice k nemoci; Adolescent; Genetic Predisposition to Disease; matrixová metaloproteinasa 2; Young Adult; genotyp; mužské pohlaví; Matrix Metalloproteinase 2; matrixová metaloproteinasa 8; promotorové oblasti (genetika); Tissue Inhibitor of Metalloproteinase-2; mladiství